ATF6 regulates cardiac hypertrophy by transcriptional induction of the mTORC1 activator, Rheb - Blackwood, Erik A.; Sandmann, Christoph; Müller, Oliver J.; Jakobi, Tobias; Dieterich, Christoph; Katus, Hugo; Doroudgar, Shirin (Circulation research, 2019)
Rationale:Endoplasmic reticulum (ER) stress dysregulates ER proteostasis, which activates the transcription factor, ATF6 (activating transcription factor 6α), an inducer of genes that enhance protein folding and restore ER proteostasis. Because of increased protein synthesis, it is possible that protein folding and ER proteostasis are challenged during cardiac myocyte growth. However, it is not known whether ATF6 is activated, and if so, what its function is during hypertrophic growth of cardiac myocytes.Objective:To examine the activity and function of ATF6 during cardiac hypertrophy.Methods and Results:We found that ER stress and ATF6 were activated and ATF6 target genes were induced in mice subjected to an acute model of transverse aortic constriction, or to free-wheel exercise, both of which promote adaptive cardiac myocyte hypertrophy with preserved cardiac function. Cardiac myocyte-specific deletion of Atf6 (ATF6 cKO [conditional knockout]) blunted transverse aortic constriction and exercise-induced cardiac myocyte hypertrophy and impaired cardiac function, demonstrating a role for ATF6 in compensatory myocyte growth. Transcript profiling and chromatin immunoprecipitation identified RHEB (Ras homologue enriched in brain) as an ATF6 target gene in the heart. RHEB is an activator of mTORC1 (mammalian/mechanistic target of rapamycin complex 1), a major inducer of protein synthesis and subsequent cell growth. Both transverse aortic constriction and exercise upregulated RHEB, activated mTORC1, and induced cardiac hypertrophy in wild type mouse hearts but not in ATF6 cKO hearts. Mechanistically, knockdown of ATF6 in neonatal rat ventricular myocytes blocked phenylephrine- and IGF1 (insulin-like growth factor 1)-mediated RHEB induction, mTORC1 activation, and myocyte growth, all of which were restored by ectopic RHEB expression. Moreover, adeno-associated virus 9-RHEB restored cardiac growth to ATF6 cKO mice subjected to transverse aortic constriction. Finally, ATF6 induced RHEB in response to growth factors, but not in response to other activators of ATF6 that do not induce growth, indicating that ATF6 target gene induction is stress specific.Conclusions:Compensatory cardiac hypertrophy activates ER stress and ATF6, which induces RHEB and activates mTORC1. Thus, ATF6 is a previously unrecognized link between growth stimuli and mTORC1-mediated cardiac growth.
Gesehen am 10.06.2019